Respuesta :
Step-by-step explanation:
[tex] \frac{3}{2} + \frac{x}{3} = \frac{11}{6} [/tex]
[tex] \frac{x}{3} = \frac{11}{6} - \frac{3}{2} [/tex]
[tex] \frac{x}{3} = \frac{11 - 3 \times 3}{6} [/tex]
[tex] \frac{x}{3} = \frac{11 - 9}{6} [/tex]
[tex] \frac{x}{3} = \frac{2}{6} [/tex]
[tex] \frac{x}{3} = \frac{1}{3} [/tex]
[tex]x = \frac{3 \times 1}{3} [/tex]
[tex]x = 1[/tex]
Answer:
x = 1
Step-by-step explanation:
3/ 2 + x/ 3 = 11/ 6
taking LCM
(9 + 2x)/ 6 = 11/ 6
multpiying both sides by 6
9 + 2x = 11
subtracting btih sides by 9
2x = 11 - 9
2x = 2
dividing both by 2
x = 1